Bamboo drilling system - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Japanese engineers have made water flow in Zambia by introducing a traditional bamboo drilling system which dispenses with metal drilling rigs, pumps, fuel oil and electricity. The Japanese team of 13 water experts started their work in a remote...